Smith and Kant: An Enquiry into the Ambivalences of Luxury (Itinera, 2025)
This study examines the concept of luxury through the contrasting perspectives of two 18th-century philosophers, exploring its moral, economic and political dimensions in the context of an emerging commercial society. Historically, luxury has been debated as both a driver of social progress and a source of inequality and moral concern. Unlike other contributors to this debate, this analysis focuses on two thinkers, Smith and Kant, who held marginal views on luxury, yet whose work reveals its complex role in liberal political theory. Smith takes an empirical approach, viewing luxury as intertwined with the rationality, sociability and sensitivity of human nature. In this view, luxury supports commerce, industry, and social refinement, ultimately benefiting society despite its association with vanity and excess. It promotes economic development, property rights, and the legal systems necessary to sustain a commercial society. Kant conceptualises luxury through a moral-philosophical lens, viewing it as a matter of duty and autonomy. He condemns luxury when it leads to excesses that are detrimental to individual dignity and communal welfare. This perspective highlights freedom, moral virtue, and culture as being essential to understanding the limits and implications of luxury. Juxtaposing these two perspectives sheds light on the differing conceptions of human nature, morality and societal progress found in modern thought. While one sees luxury as a natural and positive force in economic and social evolution, the other warns of its potential to undermine virtue and social cohesion. Together, these views provide a nuanced understanding of the ambivalent role of luxury in shaping modern liberal societies.